Disease-related stressors of caregiving burden among different types of family caregivers of persons with schizophrenia in rural China. (November 2019) - Peng, Man-Man; Chen, Hong-Lin; Zhang, Tin; Yao, Yong-You; Li, Zi-Han; Long, Lan; Duan, Qing-Qing; Lin, Fu-Rong; Zen, Ya; Chen, Jia; Ng, Siu-Man; Chan, Cecilia Lai-Wan; et al.
Background: Little is known about the impacts of schizophrenia on different types of caregiving burden. Aim: This study aims to examine how the severity of schizophrenia, social functioning and aggressive behavior are associated with caregiving burden across different kinship types. Method: The analytic sample included 300 dyads of persons with schizophrenia and their family caregivers in Xinjin, Chengdu, China. The 10th edition of the International Classification of Diseases (ICD-10) was utilized to identify the patients, whose symptom severity, social functioning and aggressive behavior were measured. Caregiving burden was estimated using the Burden Scale for Family Caregivers–short (BSFC-s). Results: A higher level of burden was significantly associated with female caregivers, larger family size, lower income, worse symptoms, poorer functional status and more aggressive behaviors. Parent caregivers showed greater burden if the patients had better functioning of social interest and concern or more aggression toward property. Mother caregivers showed greater burden than fathers. Spouses tended to perceive greater burden if the patients had better marital functioning, poorer occupational functioning or more aggressive behaviors toward property. Patients attacking others or a father with schizophrenia was related to a higher burden of child caregivers. A heavier burden of other relatives was correlated with patients' more verbal aggression and self-harm. Conclusion: This study shows the distinct impacts of disease-related factors on the caregiving burden across different kinship types. Our findings have implications for health-care professionals and practitioners in terms of developing more targeted family-based or individualized intervention to ameliorate burden according to kinship types and deal with behavioral and functional problems in schizophrenia.